2018
DOI: 10.1186/s13018-018-0852-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparing surgical interventions for intertrochanteric hip fracture by blood loss and operation time: a network meta-analysis

Abstract: BackgroundMultiple operative treatments are available for the fixation of intertrochanteric femoral fractures. This analysis was conducted to provide guidance on the appropriate clinical choice to accommodate individual patients.MethodsA systematic review was performed to identify relevant articles in databases. Randomized controlled trials (RCTs) of adults with intertrochanteric femoral fractures were eligible if they compared 2 or more of the following interventions: proximal femoral nail anti-rotation (PFNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
5
19
2
Order By: Relevance
“…In accordance with the literature, [23] we found that the mean estimated total blood loss and blood transfusion ratio were significantly lower in the PFNA group than in the DHS and PCCP groups. Contrary to the literature, [6] we found that the mean operation and fluoroscopy times were significantly higher in the PCCP group than in the PFNA and DHS groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the literature, [23] we found that the mean estimated total blood loss and blood transfusion ratio were significantly lower in the PFNA group than in the DHS and PCCP groups. Contrary to the literature, [6] we found that the mean operation and fluoroscopy times were significantly higher in the PCCP group than in the PFNA and DHS groups.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies reported that patients who had 31A1 fractures may have rather different functional outcomes following fixation with various implants. [19][20][21][22][23] The present study demonstrated that the functional outcomes in the groups were similar and satisfactory, according to the HHS. Previous reports have stated that the union time for these fractures with various implants was 12-18 weeks.…”
Section: Discussionmentioning
confidence: 66%
“…Results suggested that PCCP had the lowest probability of operative time than other treatments. However, other studies have drawn the opposite conclusion [19]. Hao et al [19] suggested that PFNA treatment results in shortest operative time than other surgical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have drawn the opposite conclusion [19]. Hao et al [19] suggested that PFNA treatment results in shortest operative time than other surgical treatments. As surgical experience might influence the operative time, thus more validation studies need to be performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation